PENGARUH KOMUNIKASI TERHADAP KEPUASAN KERJA KARYAWAN LPP RRI SORONG - Dessy Angela Magdalena Lontoh; Andrei Maryen; Lili Sarce Joi Sapari (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of communication on employee job satisfaction LPP RRI Sorong. Population and the sample in this study were all employees in the LPP RRI Sorong forty people. The analytical technique used is simple linear regression analysis and hypothesis testing using SPSS. The results of linear regression analysis then obtained the equation Y= 11,035 + 0,444x,where a =11,035 is a constant value and the result of t-test analysis shows that partially the communication variable has a positive and significant effect on employee job satisfaction with a significan value of 0,00<0,05,score tcount 4.449> from tcount 1,686 which means H1 is accepted and H0 is rejected.